RE-AFFIRMING ENGLISHNESS: ULTIMATE HALF-NESS AND (CRITICAL) MULTICULTURALISM IN BILLY BRAGG’S ENGLAND, HALF ENGLISH - Liyanti Lisda (Institut Agama Islam Negeri Palopo, 2019)
National identity in Great Britain is always interesting to discuss, as it dealt with England, Scotland, Walles, and Northern-Ireland identity, yet it is English identity that overshadowed British Identity. The problematic concept of English identity also brought up by Billy Bragg, a remarkable British musician, in his England, Half English-song in early 2000. This paper scrutinizes the question of “what does half English mean and what should be meant by full English?” using critical views on multiculturalism. The result shows that the basic idea of Bragg's works important in showing how the most changeable and essential signs of national culture and the clearer voices of its immigrant are perfect expressions of the